Description of The Degree of Stress, Anxiety and Depression in Teachers at Wahdah Islamic School 03 Makassar - Perkasa, Tegar; Jaya, Muhammad Alim; Namirah, Hanna Aulia; Bakthiar, Ilma Kherina Amaliyah; Utami, Dian Fahmi (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: The teaching profession is essential for student development but can cause stress, anxiety, and depression. Workload and professional demands contribute to emotional exhaustion, teaching burnout, and reduced teaching effectiveness, impacting both teachers’ well-being and the learning environment. Objective: To assess stress, anxiety, and depression levels among teachers at Wahdah Islamic School 03 Makassar Elementary School. Methods: A descriptive survey was conducted to evaluate the degree of stress, anxiety, and depression among elementary school teachers at Wahdah Islamic School 03 Makassar. Results: Most teachers experienced high stress, primarily due to workload and professional demands. Anxiety levels were moderate to severe in the majority of subjects, affecting performance and workplace well-being. Depression was also observed, with a small percentage showing severe symptoms, highlighting the need for psychological support. Conclusion: Teachers at Wahdah Islamic School 03 Makassar Elementary School experience significant stress, anxiety, and depression, influenced by workload and professional responsibilities. These findings emphasize the importance of implementing psychological support and mental health interventions to improve teacher well-being and maintain an effective learning environment.